Pengaruh Citra Merek Kualitas Produk dan Harga Terhadap Minat Beli Konsumen pada Resto Kayu Manis di Lamongan - Mahfud Ruris Setiaka; Puguh Cahyono (Trending: Jurnal Manajemen dan Ekonomi, 2025)
Marketing is the process of creating value for customers and building strong relationships to capture value from customers in return, (Philip Kotler, 2023). So the culinary business is a business that is in great demand, especially in the food and beverage sector because it is really needed every day and can have a big opportunity for promising results. So that in a business there is a need for buying interest, buying interest is a stage in the consumer decision making process where consumers show the intention or willingness to buy a particular product regarding that product, (Kolter and Keller, 2023). The population of this study was 1,302 buyers at Kayu Manis Restaurant in Lamongan and calculated using the Slovin formula, the sample result was 93 people. The analytical model used in this research is multiple linear regression. Based on the results of the regression test, the Y value is 1.791 + 0.377 X1 + 0.357 X2 + 0.394 X3. From this value it can be concluded that price has the highest influence on purchase interest and has the highest beta value, namely 0.394.